Histone H3K27 dimethyl loss is highly specific for malignant peripheral nerve sheath tumor and distinguishes true PRC2 loss from isolated H3K27 trimethyl loss - Marchione, Dylan M.; Lisby, Amanda; Viaene, Angela N.; Santi, Mariarita; Nasrallah, MacLean; Wang, Li-Ping; Williams, Erik A.; Larque, Ana B.; Chebib, Ivan; Garcia, Benjamin A.; Wojcik, John B. (Modern pathology, 2019)
Malignant peripheral nerve sheath tumors contain loss of histone H3K27 trimethylation (H3K27me3) due to driver mutations affecting the polycomb repressive complex 2 (PRC2). Consequently, loss of H3K27me3 staining has served as a diagnostic marker for this tumor type. However, recent reports demonstrate H3K27me3 loss in numerous other tumors, including some in the differential diagnosis of malignant peripheral nerve sheath tumor. Since these tumors lose H3K27me3 through mechanisms distinct from PRC2 loss, we set out to determine whether loss of dimethylation of H3K27, which is also catalyzed by PRC2, might be a more specific marker of PRC2 loss and malignant peripheral nerve sheath tumor. Using mass spectrometry, we identify a near complete loss of H3K27me2 in malignant peripheral nerve sheath tumors and cell lines. Immunohistochemical analysis of 72 malignant peripheral nerve sheath tumors, seven K27M-mutant gliomas, 43 ependymomas, and 10 Merkel cell carcinomas demonstrates that while H3K27me3 loss is common across these tumor types, H3K27me2 loss is limited to malignant peripheral nerve sheath tumors and is highly concordant with H3K27me3 loss (33/34 cases). Thus, increased specificity does not come at the cost of greatly reduced sensitivity. To further compare H3K27me2 and H3K27me3 immunohistochemistry, we investigated 42 melanomas and 54 synovial sarcomas, histologic mimics of malignant peripheral nerve sheath tumor with varying degrees of H3K27me3 loss in prior reports. While global H3K27me3 loss was not seen in these tumors, weak and limited H3K27me3 staining was common. By contrast, H3K27me2 staining was more clearly retained in all cases, making it a superior binary classifier. This was confirmed by digital image analysis of stained slides. Our findings indicate that H3K27me2 loss is highly specific for PRC2 loss and that PRC2 loss is a rarer phenomenon than H3K27me3 loss. Consequently, H3K27me2 loss is a superior diagnostic marker for malignant peripheral nerve sheath tumor.